(untitled) (SCIENCE TIME JOURNAL, 2026)
This study examines the didactic foundations of the formation of compensatory competence in teaching German as a second foreign language. Compensatory competence is understood as the ability of learners to overcome linguistic difficulties through the use of verbal and non-verbal strategies. The paper analyzes methodological approaches, principles, and techniques that facilitate the development of this competence. Special attention is given to multilingual learning contexts, where students already possess experience in learning a first foreign language. Practical examples illustrate how compensatory strategies can be integrated into classroom activities.